Effect of Immersive Virtual Reality on Pain and Anxiety at a Veterans Affairs Health Care Facility - Rawlins, Caitlin R.; Veigulis, Zachary; Hebert, Catherine; Curtin, Catherine; Osborne, Thomas F. (Frontiers in Virtual Reality, 2021)
Objectives The primary objective of this evaluation is to determine the impact of virtual reality (VR) distraction on acute and chronic pain in Veterans within the Veterans Affairs Health Care System (VA). A secondary objective is to determine the impact of VR on the experience of stress and anxiety in Veterans utilizing VR for the indication of pain. A third objective is to develop an understanding of the Veteran experience of using VR in a healthcare setting. Methods This prospective, pretest-posttest mixed methods assessment was performed at a VA medical center from August 30, 2019 to November 23, 2020. VR experiences lasted between 10 to 30 minutes utilizing an immersive head-mounted display with multiple, autonomously chosen virtual environments. Qualitative data was collected concurrently to provide context to quantitative measures which included pain scores and stress/anxiety levels. Data from 79 participants was included in this analysis. Data included pre- and post-VR session Defense and Veterans Pain Rating Scale and stress/anxiety levels. Results Results for the cohort demonstrated a statistically significant decrease in pain intensity (p <.001) with an average 12% decrease in pain levels and an 92% reduction in anxiety for those in concurrent pain. Conclusion VR as a non-pharmacological adjunct or alternative modality, appears to be a viable option for improving pain management and reducing anxiety in Veteran populations across various age ranges, and levels of acuity and chronicity. VR was also found to be an effective distraction from pain, a pleasurable experience for the majority, and opened the door to other non-pharmacological modalities in a Veteran population.